Something wicked - Oh, Ellen (Oh, Ellen. Spirit hunters, 2022)
Harper Raine is dealing with a lot of changes in her life, including her cousin Leo living with her and her powers becoming stronger and more unstable making her vulnerable to possession. Then she and Dayo learn of a plot to steal the youth of innocent people who use the makeup at the store where Harper's sister Kelly is working. Now the pair must stop an ancient evil and save Kelly before it's too late.